Characterization of mechanical strength and hydrogen permeability of a PdCu alloy film prepared by one-step electroplating for hydrogen separation and membrane reactors. (29th March 2019) - Endo, Naruki; Furukawa, Yoshitomo; Goshome, Kiyotaka; Yaegashi, Satoshi; Mashiko, Kin-ichi; Tetsuhiko, Maeda
Abstract: A single phase, dense PdCu alloy film was prepared by one-step electroplating. The electroplated film was easily delaminated from the SUS electrode by cutting around the edge, and the single alloy film was thus collectable. The phase structure, surface morphologies, and alloy compositions were determined by X-ray diffraction (XRD), scanning electron microscopy (SEM), and electron probe microanalysis (EPMA). The plated film before and after hydrogen permeation tests consisted of a single face-centered cubic α phase and an ordered body-centered cubic β phase, respectively. The atomic ratios of Pd and Cu were 49 and 51 at%, respectively; the Pd and Cu contents were slightly higher and lower than Pd47 Cu53, which shows the highest hydrogen permeability among Pd-Cu systems. The as-plated film exhibited high mechanical strength, and its load force at break point and displacement were 3 and 1.7 times those of the as-rolled Pd47 Cu53 films. The hydrogen permeability of the plated film with the β phase was almost the same as that of the rolled film and the values reported in literature. Highlights: Single phase, dense PdCu alloy film was prepared by one-step electroplating. The as-plated film was delaminated from the SUS electrode by cutting around the edge, yielding a single alloy film easily. XRD profile of the as-plated film showed a single FCC structure (α phase). The as-plated film showed good flexibility and mechanical strength. The obtained film is promising for use in hydrogen separation and membrane reactors.